Relevance of Spatial and Temporal Trends in Nymphal Tick Density and Infection Prevalence for Public Health and Surveillance Practice in Long-Term Endemic Areas: A Case Study in Monmouth County, NJ. Issue 4 (5th June 2022) - Jordan, Robert A; Gable, Sydney; Egizi, Andrea
Abstract: Tick-borne diseases are a growing public health problem in the United States, and the US northeast has reported consistently high case rates for decades. Monmouth County, New Jersey, was one of the earliest jurisdictions to report Lyme disease cases in 1979 and reports several hundred cases per year nearly 40 yr later. In the time since, however, tick-borne health risks have expanded far beyond Lyme disease to include a variety of other bacterial pathogens and viruses, and additional vectors, necessitating a continually evolving approach to tick surveillance. In 2017, Monmouth County initiated an active surveillance program targeting sites across three ecological regions for collection of Ixodes scapularis Say (Acari: Ixodidae) and Amblyomma americanum L. (Acari: Ixodidae) as well as testing via qPCR for associated bacterial pathogens. During the first five years of this program (2017–2021), we report high levels of spatiotemporal variability in nymphal density and infection prevalence in both species, limiting the granularity with which human risk can be predicted from acarological data. Nonetheless, broader patterns emerged, including an ongoing trend of A. americanum dominance, risks posed by Borrelia miyamotoi, and the frequency of coinfected ticks. We present some of the first county-level, systematic surveillance of nymphal A. americanum density and infection prevalence in the northeastern US. We also documented a temporary decline in Borrelia burgdorferi that could relate to unmeasured trends in reservoir host populations. We discuss the implications of our findings for tick-borne disease ecology, public health communication, and tick surveillance strategies in endemic areas.